ENTRE EL ANTI-ESPECISMO Y EL DERECHO DE LOS ANIMALES (APROXIMACIONES PARA UNA FUNDAMENTACIÓN FILOSÓFICA) (2016)
This paper presents a personal reflection on the role of non-human animals in relationships with men. In this sense, it seeks to identify some religious, legal and philosophical perspectives that allow to account for such relations; Thus, it is discussed from some moral and ethical arguments whether the inclusion of non-human animals in the legal field as true bearers of law while suffering beings is possible.As mentioned, the fundamental idea is in principle determine the role of animals within a positivized state legally, later to establish the existence of ethical and moral principles that govern man’s relationship with animals and finally, account of the importance of animal protection organizations and their impact on the construction of legal provisions in the context of their legal protection.So, the importance of this issue lies in the philosophical ius discussion of the special status of animals in relation to a policy framework and the use of the same man in research and scientific advances, so that the essence theme reflects the interest aroused by the paradigm between progress, law and philosophy and bills seeking the criminalization of animal abuse.In this vein, it is part of the following questions: Do animals suffer? If so, does it have consciousness? What religion and philosophy say? and what is the role they play in the legislation and the concept of law as things or mere property?